Wilhelm Ludwig von Eschwege und die klassische deutsche Geographie: Zur Erinnerung an seinen hundertsten Todestag - Beck, Hanno (ERDKUNDE, 1955)
Wilhelm Ludwig von Eschwege (15 November 1777 to 1 February 1855), the father of the study of the geology of Brazil, belongs to the group of scholars who helped to widen the scope of the classic German geography (1799—1859). From 1803 to 1810 he worked in Portugal and from 1810 to 1821 carried out investigations in Brazil, mainly within the area of the present day state of Minas Geraes. After his return he stimulated Alexander von Humboldt to carry out a comparison between the geology of Russia and Brazil, and he also had close contacts with Goethe.. He wrote a number of important books on Brazil and Portugal. At a time when scientific thought in Germany was dominated by influential theories, he carried out unbiased research in the field and always took pains to present the results of his investigations objectively. From 1824 to 1850 he lived mostly in Portugal and, in 1855, died in Kassel-Wolfsanger.